2021
DOI: 10.1126/sciadv.abd4676
|View full text |Cite
|
Sign up to set email alerts
|

Topography of transcriptionally active chromatin in glioblastoma

Abstract: Molecular profiling of the most aggressive brain tumor glioblastoma (GBM) on the basis of gene expression, DNA methylation, and genomic variations advances both cancer research and clinical diagnosis. The enhancer architectures and regulatory circuitries governing tumor-intrinsic transcriptional diversity and subtype identity are still elusive. Here, by mapping H3K27ac deposition, we analyze the active regulatory landscapes across 95 GBM biopsies, 12 normal brain tissues, and 38 cell line counterparts. Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 87 publications
1
16
0
Order By: Relevance
“…With this approach, we identified 1206 super enhancers in the CRC samples (Figure 7E , Supplementary Table S2 ), and 492 super enhancers in the GBM samples (Figure 7F , Supplementary Table S3 ). We also compared the list of super enhancers in our study with the reported list of super enhancers from other GBM clinical samples ( 87 ), and we found that 310 of 482 super enhancers identified in our samples overlapped with the reported super enhancers in GBM clinical samples ( Supplementary Figure S16I , Supplementary Table S4 ), which further proved the accuracy of FACT-seq in profiling H3K27ac histone modifications from FFPE samples. Among the list of super enhance genes, Tumor suppressor genes and oncogenes ( 71 ) were identified in GBM and CRC (Figure 7E , F , Supplementary Table S2, S3 ).…”
Section: Resultssupporting
confidence: 67%
“…With this approach, we identified 1206 super enhancers in the CRC samples (Figure 7E , Supplementary Table S2 ), and 492 super enhancers in the GBM samples (Figure 7F , Supplementary Table S3 ). We also compared the list of super enhancers in our study with the reported list of super enhancers from other GBM clinical samples ( 87 ), and we found that 310 of 482 super enhancers identified in our samples overlapped with the reported super enhancers in GBM clinical samples ( Supplementary Figure S16I , Supplementary Table S4 ), which further proved the accuracy of FACT-seq in profiling H3K27ac histone modifications from FFPE samples. Among the list of super enhance genes, Tumor suppressor genes and oncogenes ( 71 ) were identified in GBM and CRC (Figure 7E , F , Supplementary Table S2, S3 ).…”
Section: Resultssupporting
confidence: 67%
“…The combination of MNK inhibitors with other agents has resulted in enhanced anti-proliferative effects . The combination of MNK1/2 inhibitors and temolozomide has been reported to effectively prevent GBM cell growth in vitro . , In CML, the MNK-eIF4E axis offers an escape path to BCR-ABL inhibition by TKIs such as imatinib or dasatinib, allowing the disease to progress to blast crisis CML. The combination of MNK1/2 and BCR-ABL inhibition in a single molecule dual inhibitor or the combination of a MNK and a BCR-ABL inhibitor leads to augmented anti-proliferative effects in a mouse model of BC-CML.…”
Section: Discussionmentioning
confidence: 99%
“…MNK1/2 and their substrate eIF4E, often referred to as the MNK1/2-eIF4E axis, play a pivotal role in the regulation of protein synthesis; phosphorylation of eIF4E by MNK influences the translation of a subset of oncogenic mRNAs. A dysregulation in this pathway has been linked to cancer, , especially glioblastoma multiforme (GBM), , metabolic disorders and inflammation, autism spectrum disorder (ASD), depression, and infectious diseases …”
Section: Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the advance in surgery, radiation and immunotherapy patient prognosis is poor, with an overall survival rate of about 14 months (Preusser et al, 2011). One of the main hallmarks of glioma is its molecular diversity, due to the genomic heterogeneity and instability and to the epigenetic modifications that occur during glioma growth and development (Phillips et al, 2020; Xu et al, 2021). Epigenomic reprogramming is one of the fundamental drivers of glioma.…”
Section: Introductionmentioning
confidence: 99%